Fired Up! : A guide to transforming your team from burnout to engagement - Russell, Mia B. (De Gruyter, 2022)
Imagine this . . . you are leading a team that is full of energy, enthusiasm, creativity, cooperation, and participation. Team members enjoy working with one another and the nature of the work itself. Simply put, the team is a pleasure to engage with and they help you achieve organizational goals − on time and under budget. Sounds great - right? Of course it does . . . but it may not be your reality. Your team's success is impacted by changes within the work environment, and as a leader, manager, human resources professional or organizational development consultant you are constantly striving to address threats to employee engagement and well-being. One such threat is the global phenomenon: burnout. Fired Up! offers a framework and collection of interconnected principles that can help you build a positive and effective work environment. It serves as a starting point for people leaders (and those that work with people leaders) to understand burnout and engagement while developing a plan of action. Inspired by the stories, anecdotes, and strategies included in the book, you will find support and tools for creating an environment that fosters engagement for your team. Gain an insight into the causes and consequences of burnout, learn how to assess your team and work environment and become aware of the conditions that can shift your team from burnout to engagement.